EXPLORING THE STRENGTHS AND CHALLENGES OF RUMAH KATA SORONG: A STUDY OF A COMMUNITY READING PARK - Dayu Rifanto; Jajat Sudrajat Ardiwinata; Joni Rahmat Pramudia; Suhardi Aras (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
Papua still faces significant literacy challenges, and Community reading parks (TBMs), such as Rumah Kata Sorong (RKS), play a vital role in addressing these challenges by promoting literacy and fostering a reading culture. However, there is a lack of specific research on TBMs in Papua. Thus, a SWOT analysis of RKS is essential to develop strategic recommendations for its growth and improved impact on local literacy. This study uses a descriptive-analytical qualitative approach to explore Rumah Kata Sorong, focusing on its founder and volunteers, and aims to develop strategic recommendations to strengthen TBMs and enhance community literacy. Rumah Kata Sorong stands out among community reading parks with its curated book collection, diverse facilities, and community-driven initiatives like reading clubs and literary workshops, while also facing challenges such as limited volunteers and financial sustainability. In conclusion, RKS distinguishes itself by offering a unique collection of books, fostering reading communities, and addressing challenges such as limited management and volunteer support. The study contributes by providing a replicable model for strengthening TBMs in other regions, and by expanding the understanding of community-based literacy development in areas like Papua. Future research could explore the program's impact through quantitative analysis of community involvement and outcomes.